Exploratory Studies On Drug Abuse In The Asian Region. - Navaratnam, Profesor Madya (Dr.) V. (Pusat Penyelidikan Dadah dan Ubat-Ubatan Universiti Sains Malaysia, 1995)
The Asian Multi-City Epidemiology Study Programme entered its third year in 1996. The Asian Epidemiology Work Group (AEWG), now consisting of 22 cities has been established. A city based surveillance system has been developed in ten cities. These cities are Bangkok, Thailand; Kuala Lumpur, Malaysia; Manila, Philippines; Hanoi, Vietnam; Yangon, Myanmar; Colombo, Sri Lanka; Dhaka, Bangladesh; Kathmandu, Nepal; New Delhi, India; and Islamabad, Pakistan.